امکان تحقق علوم انسانی در امتداد تاریخی حکمت صدرایی - میثم واثقی; mohammad tschawushi (حکمت اسرا)
The humanities have emerged in the West on the basis of metaphysics and on the foundation of subjectivity. Subjectivity refers to an event in which the nature of man has changed and man has become a subject. The main purpose of the present study is to investigate the possibility of the realization of the humanities in Sadra's philosophy with a different approach from the common one. The approach of this exploration is based on a special interpretation of philosophy called hermeneutic phenomenology. This approach seeks to explore how to create something by exposing its foundation. According to this approach, if one can expect the realization of the humanities along the historical line of Sadra's philosophy, Sadra's philosophy also contains the subjective element. The author believes that Sadra's philosophy has this element. Therefore, through the phenomenological method, two evidences were made on this claim. The focus of the evidence presented is the distinction that Sadra's philosophy has found with regard to theoretical mysticism and Ibn Sina’s philosophy. The presented evidence shows that as a result of the developments of Sadra's philosophy, the essence of truth (Haq) is exposed from the mystery and transcendence that it was in Ibn Sina’s philosophy and theoretical mysticism and posed in consciousness.